Combination Versus Monotherapy for Carbapenem-Resistant Acinetobacter Species Serious Infections: A Prospective IPTW Adjusted Cohort Study - Manesh, A; George, MM; Palanikumar, P; Nagaraj, V; Bhanuprasad, K; Krishnan, R; Nivetha, G; Lal, B; Triveni, KR; Gautam, P; George, B; Kulkarni, U; et al. (Springer, 2024)
Introduction: International guidelines recommend definitive combination antibiotic therapy for the management of serious infections involving carbapenem-resistant Acinetobacter (CRAB) species. The commonly available combination options include high-dose sulbactam, polymyxins, tetracyclines, and cefiderocol. Scanty prospective data exist to support this approach. Methods: Patients with CRAB bacteraemia, ventilator-associated pneumonia (VAP), or both were categorized based on whether they received combination therapy or monotherapy. The 30-day mortality was compared between the two groups. Inverse probability treatment weighting (IPTW) was done using propensity score (PS) for a balanced comparison between groups. Results: Between January 2021 and May 2023, of the 161 patients with CRAB bacteraemia (n = 55, 34.2%), VAP (n = 46, 28.6%), or both (n = 60, 37.3%) who received appropriate intravenous antibiotic therapy, 70% (112/161) received monotherapy, and the rest received combination therapy. The overall 30-day mortality was 62% (99/161) and not different (p = 0.76) between the combination therapy (31/49, 63.3%) and monotherapy (68/112, 60.7%) groups. The propensity score matching using IPTW did not show a statistical difference (p = 0.47) in 30-day mortality for receiving combination therapy with an adjusted odds ratio (OR) P of 1.29 (0.64, 2.58). Conclusion: Combination therapy for CRAB infections needs further study in a randomised controlled trial, as this observational study showed no difference in 30-day mortality between monotherapy and combination therapy.